Kepercayaan dan Praktik Budaya dalam Film Tari Kematian: Pendekatan Antropologi Sastra Victor Turner - Maksum, Siti Rohmatun; Putri, Gita Ananda; Efendi, Agik Nur (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Jember, 2025)
This research explores the representation of cultural symbolism and traditional beliefs in the film Tari Kematian (Death Dance) through the lens of Victor Turner’s theory of literary anthropology. Employing a descriptive-qualitative method, the study focuses on interpreting scenes, dialogues, and symbolic elements. The analysis shows that sacred rituals, transitional ceremonies, and cultural prohibitions embody liminal experiences and the emergence of social bonds. The narrative underscores the significance of honoring sacred traditions and highlights the social tensions that may arise when cultural boundaries are crossed. Ultimately, the film is seen as a vehicle for sustaining and expressing local cultural identity.